2021
DOI: 10.1017/jog.2021.15
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the bias of TanDEM-X digital elevation models of glaciers on the Tibetan Plateau: impacting factors and potential effects on geodetic mass-balance measurements

Abstract: The TanDEM-X DEM is a valuable data source for estimating glacier mass balance. However, the accuracy of TanDEM-X elevation over glaciers can be affected by microwave penetration and phase decorrelation. To investigate the bias of TanDEM-X DEMs of glaciers on the Tibetan Plateau, these DEMs were subtracted from SPOT-6 DEMs obtained around the same time at two study sites. The average bias over the studied glacier areas in West Kunlun (175.0 km2) was 2.106 ± 0.012 m in April 2014, and it was 1.523 ± 0.011 m in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…Thus, the differences in backscatter intensity could be caused by either accumulation of fresh snow at the glacier surface or days with snowmelt during September 2016. It is likely that the depth of signal penetration in the winter seasons 2010/11 and 2016/17 was relatively large, i.e., several meters, as found by previous studies (Millan et al, 2015;Zhao and Floricioiu, 2017;Abdullahi et al, 2018;Li et al, 2021), but similar due to comparable dry and frozen surface conditions. For TanDEM-X DEMs of the Antarctic Peninsula it was observed that the measured coldseason heights rather referred to the refrozen firn of the previous summer than to the actual glacier surface (Rott et al, 2014).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Thus, the differences in backscatter intensity could be caused by either accumulation of fresh snow at the glacier surface or days with snowmelt during September 2016. It is likely that the depth of signal penetration in the winter seasons 2010/11 and 2016/17 was relatively large, i.e., several meters, as found by previous studies (Millan et al, 2015;Zhao and Floricioiu, 2017;Abdullahi et al, 2018;Li et al, 2021), but similar due to comparable dry and frozen surface conditions. For TanDEM-X DEMs of the Antarctic Peninsula it was observed that the measured coldseason heights rather referred to the refrozen firn of the previous summer than to the actual glacier surface (Rott et al, 2014).…”
Section: Discussionsupporting
confidence: 51%
“…In general, SAR penetration is close to zero for melting snow surfaces and bare glacier ice and increases in dry snow. Xband penetration depths of several meters have been observed in different regions (e.g., Millan et al, 2015;Zhao and Floricioiu, 2017;Abdullahi et al, 2018;Li et al, 2021). Previously, penetration depths have been estimated by a number of studies (e.g., Abdullahi et al, 2018Abdullahi et al, , 2019Li et al, 2021) using backscatter intensity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are only able to provide a region-wide mass balance estimate when aggregated over sufficiently large regions so that glaciers (in particular the different elevations bands) are well sampled. The denser sampling by CryoSat-2 swath altimetry and ICESat-2 allows resolving regions of 100 by 100 km and infer the seasonal elevation changes (Jakob et al 2021, Wang et al 2021. For ICESat, the spatial sampling was sparser and temporally more irregular so that mass loss estimates were mostly restricted to a single value (for the period 2003-2008) over large regions (Kääb et al 2015).…”
Section: Comparison Over the Everest Area-himalayamentioning
confidence: 99%
“…where l is the length of the glacier/lake boundary and r is the image resolution. The uncertainty of the average glacier elevation (δ average ) was calculated on the basis of the uncertainty of the elevation difference over stable regions and the spatial autocorrection of the elevation difference [7,43]. The computation formula is…”
Section: Uncertainty Analysismentioning
confidence: 99%